(untitled) (LACCEI, 2024)
The objective is to increase the export level of the grapes of an agro-export company located in Ica-Peru, based on the optimization of the supply chain management, which takes as a principle the processes of supply, productivity and distribution, so that It seeks to achieve greater export efficiency, reducing its costs and quickly adapting procedures in the logistics area. The method used has a descriptive scope based on a mixed perspective and a non-experimental design, of applied typology. The instrument used in the data collection was the interview with the administrative staff of the logistics area, identifying the problems based on the dimensions that the supply chain covers in provisions, organization and planning, which generates an increase in time and costs. costs at the end of the chain in productivity. The results identify that the company does not take advantage of 100%, meaning a high growth potential that is based on the positioning of the grape in the national market and the progressive demand in the international arena. In the aspect of distribution and supply, there is no schedule for the dispatch that is used to guide and avoid delays in the delivery of orders. concluding that an adequate management of the supply chain in a grape agro-export company will favor the optimization of the processes that indirectly increase the periodic export of the product. The disorganization and insufficiencies in the organization limit from its conformation a greater expansion in the market, so by achieving greater effectiveness and efficiency. The development of production processes and export activity is intended.